AVALIAÇÃO DE EMISSÕES FUGITIVAS DE BIOGÁS DE ATERRO SANITÁRIO EM CAMADA DE COBERTURA CONVENCIONAL E COM CARACTERÍSTICAS MELHORADAS APLICANDO MÉTODO DE CÂMARA DE FLUXO EM REGIME ESTÁTICO - FRANQUETO, RAFAELA (2016)
Gas emissions in landfills resulting from the anaerobic decomposition of municipal solid waste (MSW) and, as a byproduct of this degradation has been the generation of biogas. Nearly all of the residual mass from biogas is emitted to the atmosphere as emission point (the landfill drainage system) and fugitive, in this case, the cell of the cover layer. To mitigate fugitive emissions, studies including the biological oxidation of methane in the covering layer have been developed. In this study, we assessed, using flow chamber operating in static regime, the oxidation capacity of the cover layer of a subtropical fill under normal conditions (control area) and modified (improved by organic material addition) by determinations of the concentration of the biogas amount ("raw biogas") and downstream of this layer. They also assessed the methane concentration profiles at different depths in the areas of control and modified compared to raw biogas, in order to determine the optimum range methane oxidation in the thickness of the layer evaluated. The methane oxidation efficiency (Fo) of the measured areas was similar: 99.5% (control area) to 100% (improved) for medium flow 37.0 and 23.0 g / (m2.d) respectively. The main factors that favored higher oxidation efficiency (Fo) of methane in the modified area were the addition of organic matter and the higher average moisture content of this area. The soil layer of modified area can be considered an innovative alternative and cost effective for the treatment of diffuse methane emissions from landfills, minimizing emissions of greenhouse gases and is an alternative for small and medium landfills sizes, taking into account also the requirements of the National Solid Waste Policy in Brazil (Law 12.305 / 2010).